Perbedaan pemenuhan kebutuhan dasar anak yang diasuh orangtua dengan yang diasuh di taman penitipan anak (TPA) terhadap status gizi dan perkembangan anak usia 24 bulan di kecamatan godean - Awwalul Wiladatil Qodliyah (Sinar : Jurnal Kebidanan, 2022)
The problem of child development growth disorders increases especially with psychosocial backgrounds that are not good due to parental care and fulfillment of the child's basic needs which include love, teach and care. The purpose of this study is to determine the difference between the fulfillment of children’s basic needs who are raised by parents and those who are raised in daycare with nutritional status and development of 24-month-old children in Godean District. This study employed a cross sectional design with a sample size of 60 respondents and was conducted in 6 village in Godean District. Univariate analysis was presented with a frequency distribution table, bivariate analysis with the Mann Whitneyy test. The results of the analysis of fulfilling children’s basic need showed that there were no differences between the children who were raised in daycare and those who were raised by parents with p-value = 0.124. In the nutritional status variable, the children who were raised in daycare and those who were raised by parents had no difference with the p-value = 0.797. In the development of children variable, the children who were raised in daycare and those who were raised by parents had no difference with the p-value = 0.180. In the outside variables, there was no difference between economic status, children health history and mothers’ education the child raised in daycare and those who were raised by parents with p-value = 0.200 for economic status, p-value = 0.776 for medical history and p-value = 0.792 for mother's education. There was no difference between the place of care and the nutritional status and development of the children. There was no difference between the external variables that affected the 24-month-old children who were raised in daycare and the children who were raised by parents in Godean District.